Children's Constitutional Rights in the Nordic Countries - Haugli, Trude; Nylund, Anna; Sigurdsen, Randi; Bendiksen, Lena R. L. (Stockholm Studies in Child Law and Children's Rights, 2019)
This study explores whether and how enshrining children's rights in national constitutions improves implementation and enforcement of those rights by comparing Danish, Finnish, Icelandic, Norwegian and Swedish law. Readership: All interested in children's rights, human rights and constitutional law. Politicians, academic libraries, researchers, students, practitioners in law.